Demand for Natural Gas in Food and Beverage Industries of Iran - Agheli, Lotfali (International Journal of Energy Economics and Policy, 2016)
Food and beverage industries play crucial roles in satisfying food requirements. They rely on various kinds of energy to prepare and process foodstuff. The relative prices, technology level, sector growth and machinery status determine use of energy carriers in these enterprises. This paper examines the relationships among natural gas use, value-added and energy prices in food and beverage industries of Iran during 1978-2014. The decision unit is food manufacturing workplace. By considering microeconomic basics and applying co-integration approach, demand for natural gas is estimated. Due to the long-run nature of co-integrating relationships, the long-run own- and cross- price elasticities and income elasticity are estimated. Our findings show that natural gas is a luxury input in food industry, it is highly elastic to its price; and electricity and oil products are substitutes for natural gas. In a growing food sector, we would expect natural gas use to increase more rapidly. Keywords: Natural Gas, Food industry, Price elasticity JEL Classifications: D21, Q13, Q41